Some particularities of dam rehabilitation projects - Budweg, F. M.G. [UNESP] (My University, 1999)
The number of dams, which need rehabilitation, is growing, not only in countries that have a long tradition in dam building and operation but also in those regions where the infrastructure is still in full development. Though rehabilitation projects generally deal with problems that are common in dam engineering practice, there are some peculiarities which are a characteristic of such projects and which must be duly taken into account to avoid unsuccess and/or unnecessary costs. Regular safety inspection is essential to forestall the development of structural, hydrological and operational unsafety. If need of major repair or overall rehabilitation of a dam becomes apparent design of the rehabilitation project must be preceded by a comprehensive checkup of the structure and appurtenant works, as well as by an evaluation of its hydrological safety inclusive of all relevant environmental aspects. The availability of complete records on the dam's structural behaviour and on meteorological and hydrological data, as well as the knowledge of the materials properties of the existing structure are important for the successful design of a rehabilitation project. To this end the installation of monitoring devices in the existing structure may be necessary to generate representative data. While the criteria to be used in structural design should correspond to current standards, the definition of hydrological design criteria depends on considerations that vary widely from region to region or even from one country to another. Some basic hydrological safety requirements, however, are recommended for general acceptance. Dam rehabilitation projects demand very careful and detailed construction planning because of their dependence on river flow conditions, operational restrictions and, often, on procedures or limitations imposed to avoid harm to the environment. Of utmost importance is the timely availability of the financial funds required to complete the project, in order to avoid delays which could result in structural or operational unsafety. Since every dam sooner or later will have to undergo major repair or updating of safety, rehabilitation may evolve to a speciality of dam engineering.